The Urgency of Digital Literacy for Early Childhood - Widya Khairunnisa; Munisa Munisa (International Journal of Educational Evaluation and Policy Analysis, 2025)
Young children's lives have been profoundly impacted by the quick growth of digital technology in the age of globalization, especially in light of their easy access to electronic gadgets like computers, tablets, and smartphones. Early childhood education has additional difficulties as a result of this circumstance, particularly with regard to digital literacy. The ability to properly comprehend, use, and critically assess digital information is a crucial component of digital literacy. Lack of this ability puts children at risk for negative effects include exposure to unsuitable content for their age, trouble sifting information, and gadget addiction. This study used a library research approach to investigate the importance of digital literacy for young children. The results showed that in order to enhance children's cognitive, social, and emotional development in the digital age, digital literacy must be ingrained from a young age. Additionally, digital literacy is anticipated to be a key component in preparing Indonesia's Golden Generation of 2045, allowing children to develop into critical, imaginative, and astute tech users.